Effects of Fiscal Policy on Economic Growth in Nepal - Santosh Khanal; Pramshu Nepal (Prāgyik Prabāha, 2024)
Fiscal policy is the most important tool of government that influences economic activity through public spending, taxation, and public debt. The primary goal of Nepalese fiscal policy is to achieve high, sustainable, and inclusive economic growth by boosting private sector confidence, reducing transaction costs, and improving public spending effectiveness. The main objective of present paper is to examine the relationship between the different fiscal policy variables and how they impacts growth of the country. The study applied descriptive and causal relationship research design.To accomplish the objective, the secondary data from 1974–1975 to 2021–2022 were poised.The findings suggested a co-integration between the dependent and independent variables as well as a long-term relationship between the variables. The estimated coefficients of GTAX and RNETFL show the response to Nepal's RGDP. It showed that one percent increase in government tax revenue raises GDP by 0.2489 percent. Similarly, one percent increasing in the net outstanding foreign loan (NETFL) increases RGDP by.0613 percent. As a result, independent variables such as government tax and net outstanding foreign loans both contribute to Nepal's GDP. These findings should encourage those responsible for developing fiscal policy to create taxes, spending plans, and proper use of foreign loans to protect productive spending while avoiding tax structures targeted explicitly at the country's low[1]income households.